Adrenergic mechanism of femoral arterial constriction during carotid occlusion in dogs1 - Chen Da-Guang; Carlyle Peter; Carlyle Wenda; Eekhoff Patricia; Cohn Jay N (Acta Pharmacologica Sinica, 2016)
occlusion (BCO) was studied in 17 anesthetized dogs. When the perfusion pressure was kept constant the femoral resistance increased, which was different from that when the perfusion pressure was allowed to rise. Plasma NE increased at 60 and 120 s of BCO. The elevation of systemic blood pressure occurred before the change of NE. Yohimbine (Yoh, α2 antagonist) and indoramin (Ind, α1 antagonist) caused the reduction of femoral vascular resistance (FVR) by 24 and 27%, respectively, and the combination of the two drugs by 38%. In the presence of Ind and Yoh, the dose-response curves (DRC) of phenylephrine shifted rightward as the equipotent doses increased 25-30 folds, respectively； the DRC for azepexole shifted rightward as well but the equipotent dose increased 6 folds only in the presence of Ind, and almost 30 folds in the presence of Yoh. Thus it is concluded that BCO appears to result in neurally mediated stimulation of both postsynapticα1 andα2 adrenergic receptors.